Financial development and economic growth: the experiences of selected OIC countries - Duasa, Jarita (2013)
The financial sector, the money and capital market, has developed so much to the extent that it’s been said as being in the transition continuously and there is always a demand for it. The financial system keeps changing and within a year, various types of new financial tools being introduced in the market. Moreover, the size of transaction taking place is so large, that it could affects the economy positively. If financial development causes economic growth, this is in line with the “supply-leading” views, whereas if economic growth causes financial development, then it is suitable with the “demand-following” views. Focusing on selected OIC countries, the present study aims to investigate the impact of financial development on economic growth or vice versa, in respective countries. Data collected are ranging from 1960-2005 for each country and only countries which have sufficient data (minimum of 30 years) are selected and used in the analysis. Base on this, we select the following countries in this study: Bahrain, Egypt, Iran, Jordan, Kuwait, Libya, Malaysia, Pakistan, and Saudi Arabia. Using vector autoregressive model (VAR) and vector error correction model (VECM), the above hypotheses are re-examined concerning the relationship between financial development and economic growth. The study finds that for Malaysia and Egypt, there is bi-directional causality between financial development and economic growth. Results on Iran and Jordan indicate unidirectional causality which supports the “demand-following” views, while Bahrain, Kuwait, Libya, Pakistan and Saudi Arabia signify no exact Granger-causality relationship between the two variables. In addition, with the VECM results, the error correction terms for Jordan and Kuwait are found to be significant, implying that there is a long run relationship between variable in at least one direction for each country.